Sustainable design: exploration of recycled materials physical forms in furniture studies / Nurul ‘Ayn Ahmad Sayuti, Shahriman Zainal Abidin - Ahmad Sayuti, Nurul ‘Ayn; Zainal Abidin, Shahriman (Institute of Research Management & Innovation (IRMI), 2011)
Waste is not a waste when it can become a new transformation of products and giving a new function and this will help to reduce the environmental issues, preserving for the next generation and give benefits to the country in economy sector. One of the key benefits of recycling comes from reducing the amount of new material required. In theory, recycling allows a material to be continually reused for the same purpose (Dictionary.com). According to Datschefski (2001) in his book the Total Beauty of Sustainable Products, “Products are the source of all environmental problems. Major issues such as pollution, deforestation, species loss, and global warming are all side-effects of the activities that provide consumers with food, transport, shelter, clothing and the endless array of consumer goods on the market today.../ called this the ‘Hidden Ugliness’ of products". An individual product which looks harmless may causes the environmental damages. The objectives of this research are to identify suitable and proper materials that can be recycled and reused to produce furniture design, to explore the flexibility of the recycled materials physical forms in producing furniture design and to identify the flow of design that can be achieved by recycled materials in producing furniture design. This research started with collection of secondary data such as journals, books, magazine, reports, websites and articles. Then the researcher gathered information from semi structured interview, questionnaires and observation of products and other related information. As all have been gathered, the researcher will analyse and clarify the data using a research methodology of empirical method of qualitative research through descriptive and experimental research.